Three Decades of Auxetics Research − Materials with Negative Poisson's Ratio: A Review - Saxena, Krishna Kumar; Das, Raj; Calius, Emilio P. (Advanced engineering materials, 2016)
Material properties can be tailored through modification of their geometry or architecture. With this concept, a lot of smart materials, metamaterials, and smart structures have been developed. Auxetic materials and structures are a novel class of materials which exhibit an interesting property of negative Poisson's ratio. By virtue of the auxetic behavior, mechanical properties such as fracture toughness, indentation resistance, etc., can be improved. In order to exploit the interesting properties of auxetic materials, several potential applications of auxetic materials have been explored in medical, sports, automobile, defense, etc. Design and modeling of novel auxetic materials and structures is still on the way. Here, the article focuses upon the different aspects of auxetic materials and structures. A comprehensive updated review of auxetic materials, their types and properties, and applications has been presented. This paper also discusses the design and modeling approaches of auxetic structures. Auxetic materials possess an interesting property of negative Poisson's ratio. By virtue of this negative Poisson's ratio, several other mechanical properties can be enhanced. This review presents briefly the current state of the art and progress in the auxetics research made in the past three decades. The review attractively covers most of the aspects of auxetic materials such as classification, structure, properties, applications, design, and modeling.